Cocaine treatment admissions at three sentinel sites in South Africa (1997-2006): findings and implications for policy, practice and research. - Parry, C.D.H.; Plüddemann, A.; Myers-Franchi, Bronwyn (BIOMED CENTRAL LTD, 2007)
BACKGROUND: Accurate prevalence data on cocaine use, that points to where problems exist and the extent of these problems, is necessary to guide the formulation of effective substance abuse policy and practice. The purpose of this study was to provide surveillance information about the nature and extent of problematic cocaine use in South Africa.